PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITAS, INVENTORY INTENSITY, CAPITAL INTENSITY DAN LEVERAGE PADA AGRESIVITAS PAJAK - Andhari, Putu Ayu Seri; Sukartha, I Made (E-Jurnal Akuntansi, 2017)
Targets of President Joko Widodo related  to taxation is striking a tax ratio of 16% in 2019. But it is still impeded because there are indications that the company is still trying to commit acts of aggression taxes. The purpose of this study was to obtain empirical evidence of the influence of CSR, profitability, inventory intensity, capital intensity and aggressiveness leverage on taxes. This research used non-probability sampling method, and using purposive sampling technique. The analysis technique used descriptive  and multiple linear regression analysis. The results of this study the variables of profitability and capital intensity positive effect on the aggressiveness of corporate tax, while variable leverage CSR disclosure and negative effect on the aggressiveness of corporate tax, and inventory variable intensity had no effect on the aggressiveness of the tax.
Keywords: CSR, profitability, inventory, capital, leverage, tax aggressivenessffect on the aggressiveness of the tax